2011
DOI: 10.1080/10875301.2011.597632
|View full text |Cite
|
Sign up to set email alerts
|

Burning the Midnight Oil: Librarians, Students, and Late-Night Chat Reference at the University of Notre Dame

Abstract: m. until 1 a.m. Sunday through Thursday evenings during the academic year. Data showed that the number of questions asked during late-night chat hours was comparable to the number being asked during regular reference chat hours. Findings showed that the complexity of the chat questions being asked after hours was greater than that of chat questions asked during regular hours and that of reference desk transactions as a whole. Late-night chat reference was a valuable exercise in meeting users at their point of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…Belanger et al (2016), Gerlich and Berard (2010), and Maloney and Kemp (2015) each analyzed the READ Scale ratings by point in the academic semester or quarter in order to understand the relationship between the academic calendar and the complexity of reference transactions. Cabaniss (2015), Kayongo and Van Jacob (2011), and Ward and Jacoby (2018) compared ratings across times of day in order to understand busyness patterns by hour. Cabaniss ( 2015) also looked at days of the week in order to find the busiest and least busy days.…”
Section: Data Points Used In Conjunction With Read Scalementioning
confidence: 99%
See 1 more Smart Citation
“…Belanger et al (2016), Gerlich and Berard (2010), and Maloney and Kemp (2015) each analyzed the READ Scale ratings by point in the academic semester or quarter in order to understand the relationship between the academic calendar and the complexity of reference transactions. Cabaniss (2015), Kayongo and Van Jacob (2011), and Ward and Jacoby (2018) compared ratings across times of day in order to understand busyness patterns by hour. Cabaniss ( 2015) also looked at days of the week in order to find the busiest and least busy days.…”
Section: Data Points Used In Conjunction With Read Scalementioning
confidence: 99%
“…Similarly, Bungaro et al (2017) found evidence to maintain and keep subject librarians answering a subjectspecific chat channel, whereas they assumed generalist librarians could adequately answer READ Scale 1-3. Further evidence was found to keep professional librarians answering chat, arguing that outsourcing late night chat service to consortial librarians resulted in decreased quality of service (Kayongo & Van Jacob, 2011).…”
Section: Staffing Needsmentioning
confidence: 99%
“…Kayongo and van Jacob (2011) examined late-night chat service at Hesburgh Library at the University of Notre Dame, which was well-used during the two and a half years it was available. Due to staffing constraints, Hesburgh Library eventually had to discontinue this service, but their case study provides a good example of how considerations unrelated to the value of a service affects reference practices other than the desk (Kayongo & van Jacob, 2011, p. 108).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research on reference during nonbusiness hours are often part of a study or short-term trial, such as Direct-2-U reference in residence halls at the University of Texas at San Antonio (Del Bosque & Chapman, 2007), late night online service from 9:00 p.m. to 1:00 a.m. at Notre Dame University (Kayongo & Jacob, 2011), or the University of Buffalo's providing onsite reference and instruction in department spaces (Wagner & Tysick, 2007). These three studies provide insight to confirm that reference services are needed both in the evening and in other non-library spaces.…”
Section: Literature Reviewmentioning
confidence: 99%